2010
DOI: 10.1159/000276402
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness in Parkinson’s Disease: Characteristics and Determinants

Abstract: Background/Aims: Excessive daytime sleepiness (EDS) is frequent in patients with Parkinson’s disease (PD). Occasionally, EDS in PD exhibits narcolepsy-like features. We aimed to assess characteristics and determinants of EDS in consecutive patients with PD. Methods: Thirty consecutive patients with PD underwent a detailed clinical examination. EDS was assessed using the Epworth Sleepiness Scale (ESS) and Multiple Sleep Latency Test (MSLT). Sleep was assessed using video-polysomnography. Cerebrospinal fluid (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 71 publications
3
82
1
3
Order By: Relevance
“…The occurrence of EDS among patients with PD was lower in Asian than in Caucasian populations in the literature. Studies from Asia using the ESS have reported that the prevalence of EDS ranged from 15.1% to 32.3%; however, prevalence ranging from 40.6% to 57% was reported for Europe and North America (Brodsky et al., 2003; Chen et al., 2015; Goldman et al., 2013; Hobson et al., 2002; Louter et al., 2012; Poryazova et al., 2010; Ratti et al., 2015; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016) (Table 3). Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The occurrence of EDS among patients with PD was lower in Asian than in Caucasian populations in the literature. Studies from Asia using the ESS have reported that the prevalence of EDS ranged from 15.1% to 32.3%; however, prevalence ranging from 40.6% to 57% was reported for Europe and North America (Brodsky et al., 2003; Chen et al., 2015; Goldman et al., 2013; Hobson et al., 2002; Louter et al., 2012; Poryazova et al., 2010; Ratti et al., 2015; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016) (Table 3). Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy. The disease severity of the patients were similar in these Western and Asian studies, with H&Y stages between 2 and 3 (Poryazova et al., 2010; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016). In a study of 638 Canadian patients with PD with H&Y stage of 2.2 ± 0.68, Hobson et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that high doses of medications were associated with daytime sleepiness in accordance with other previous studies. 32,33 Although daytime sleepiness followed by nocturnal sleep disturbance has a large impact on quality of life in PD, control of medication-related daytime sleepiness may not be simple because high doses of antiparkinsonian medication may be necessary to reduce severe motor symptoms.…”
Section: Discussionmentioning
confidence: 99%